(untitled) (Update Dental College Journal, 2014)
Among all the life threatening diseases, autoimmune diseases are among most notorious and complicated diseases. As these diseases have no specific cause or responsible organism, it is therefore very difficult to distinguish and diagnose and thus stands as a major threat for public health. It is assumed that the reason for these diseases may be from genetic to environmental factors, from stress to idiopathic origin. Pemphigus Vulgaris(PV) is such an autoimmune blistering disease that frequently affects the mucous membrane and skin. Very often it starts from oral cavity and Dentists therefore the first to recognize. This paper describes the case of a patient presenting with a one-year history of painful ulcerated gingiva, tongue, floor of the mouth and even on GIT who is finally diagnosed as having PV spreading to generalized skin. DOI: http://dx.doi.org/10.3329/updcj.v3i2.17999 Update Dent. Coll. j: 2013; 3 (2): 43-47